Grabbing Dignity - Roa Pilar, Cristian Felipe (Journal of Anthropological Films, 2017)
‘Grabbing Dignity’ explores how marginalised women perceive their dignity during a relocation process from an illegal settlement to subsidised housing in Santiago, Chile, in 2016. Through an ethnographic-based approach, the film experiments with different audiovisual language techniques, where observational cinema, semi-structured interviews and voice over are combined to build a reflective storytelling about a year-long fight for housing rights. This film points out that the fight for dignity is not driven by seeking material goods for improving their quality of life, but rather as finding a legitimate and embodied sense of place where the locals are accepted by the wider Chilean society, and by that acceptance also recognised as human beings. I portray that this fight is contrasted by how the relocation is carry out by the Chilean government where house and home are inaccurately taken as equals. With this in mind, the film enlarges the discussion about human dignity as not only an individual perception, but also as a community-based phenomenon. From this perspective, I suggest that a collective sense of place is paramount in achieving a better understanding of what human dignity might encompass.